COOPEITION: A CONTENT ANALYSIS STUDY WITHIN THE SCOPE OF EMPIRICAL ARTICLES PUBLISHED BETWEEN 2010-2020 (Third Sector Social Economic Review, 2020)
The concept of coopetition, which is frequently emphasized in the literature as a paradoxical phenomenon, has continued to attract the attention of the academic world and researchers for many years. With this study, it is aimed to develop a broader understanding of coopetition and to shed light on future studies. In this study, a content analysis covering the empirical articles published in foreign literature between 2010 and 2020 in the context of management and organization for the concept of coopetition was conducted systematically and classified according to their basic context. The empirical studies reviewed show that firms' competitiveness is not limited to certain sectors. The findings also reveal that coopetition has some difficulties in practice (such as redefining organizational boundaries, establishing a trust relationship and coordination of coopetition) and contradictions (such as cooperation and information sharing with competitors). In light of the findings, coopetition can generally be considered as a phenomenon that includes the structural and behavioral dimensions as well as being a strategic choice with a competitive dimension.
Keywords: Coopetition; management and organization; content analysis